Host Immunity to Malassezia in Health and Disease - Sparber, Florian; Ruchti, Fiorella; LeibundGut-Landmann, Salomé (Frontiers in Cellular and Infection Microbiology, 2020)
The microbiota plays an integral role in shaping physical and functional aspects of the skin. While a healthy microbiota contributes to the maintenance of immune homeostasis, dysbiosis can result in the development of diverse skin pathologies. This dichotomous feature of the skin microbiota holds true not only for bacteria, but also for fungi that colonize the skin. As such, the yeast Malassezia, which is by far the most abundant component of the skin mycobiota, is associated with a variety of skin disorders, of which some can be chronic and severe and have a significant impact on the quality of life of those affected. Understanding the causative relationship between Malassezia and the development of such skin disorders, requires in-depth knowledge of the mechanism by which the immune system interacts with and responds to the fungus. In this review, we will discuss recent advances in our understanding of the immune response to Malassezia and how the implicated cells and cytokine pathways prevent uncontrolled fungal growth to maintain commensalism in the mammalian skin. We also review how the antifungal response is currently thought to affect the development and severity of inflammatory disorders of the skin and at distant sites.